Desafios às práticas docentes inclusivas no Instituto Federal da Paraíba - Nóbrega, Carina Alessandra da (2023)
Faced with the challenges encountered by people with disabilities to ensure that their right to education is respected, it can be seen that inclusive education is a policy still under construction in Brazil. Bearing in mind the importance of the inclusion policy for the process of democratization of higher education, this research deals with the theme of inclusive education in higher education and proposes to contribute to the advancement of the construction of inclusive practices in Higher Education Institutions. The present study presents an exploratory and descriptive research with an applied nature and a qualitative approach. Thus, as a general objective, it aims to analyze the challenges faced by teachers in front of students with disabilities, at the Federal Institute of Education, Science and Technology of Paraíba (IFPB), João Pessoa campus. As specific objectives, the study intends to know the teachers' conceptions about inclusion/exclusion in classes; to list the barriers found for the construction of inclusive practices for students with disabilities and to identify the teachers' knowledge about the existing resources in the institution that can help in inclusive teaching practices for these students. The survey was carried out with seven IFPB professors and was collected through an electronic questionnaire. The collected data were analyzed using the content analysis model proposed by Bardin as a guide. The research pointed out that participating teachers feel the need to know in advance which students with disabilities will participate in their classes and how they can make their classes inclusive and accessible to all students. Participants showed interest in participating in ongoing training to promote the improvement of their inclusive actions. Faced with the formative searches emanating from the empirical field itself, this research resulted in the creation of a repository of courses, aimed at higher education professors, emphasizing the importance of training and presenting a catalog of online courses available to professors to improve their skills. practices. The site has courses on inclusion of students with disabilities and inclusive teaching practices that can help them improve their inclusive practices in higher education.